Assessment of Medical Students' Knowledge and Access to Scientific Journal Articles in Jordan: Insufficient Knowledge Has Potentially Negative Effects on the Social Response to COVID-19. Issue 4 (2nd October 2022) - Ashour, Laith; Funjan, Khaled
Abstract: This study aims to evaluate medical students' impressions and attitudes toward scientific journal articles, and their accessibility to them in one of the developing countries, Jordan. Fourteen questions were asked to medical students to assess their knowledge and accessibility to papers, and to discover the impact of low interest in scientific papers on students' dealing with COVID-19. Data were analyzed using descriptive and analytical statistics. The study found that there is an unsatisfactory reading for scientific journal articles among medical students, with only 47.2% of students reading them. Furthermore, there are unsatisfactory results regarding students' knowledge about journal types from the trust perspective (i.e., predatory and reliable journals). This was mainly because of a lack of adequate universal teaching about scientific journal articles, as 86.7% of medical students reported that their universities do not teach them about scientific journal articles. The absence of comprehensive learning about scientific journal articles had a potential negative impact on the medical student's handling of COVID-19 socially (i.e., advising people in the community about vaccination importance, social distancing, and other preventive measures). Librarians should be involved primarily in undergraduate education related to scientific journal articles, and their role in providing subscription-based journals free of charge, as well as protecting students from predatory journals through suitable library instructions, is essential.